Faktor-faktor yang Berpengaruh terhadap Peringkat Obligasi (Studi pada perusahaan Manufaktur yang terdaftar di BEI) - Widiyastuti, Tetty; Khusniyah, Nur; Djumahir (Jurnal Aplikasi Manajemen, 2014)
This research aim to identify the factors affecting obligation rank on manufacturing corporations. The factors investigated in this research include coverage ratio, liquidity ratio, solvability ratio, productivity ratio, and business risk. The population in this research is all manufacturing corporations registered in BEI, with the first criteria is the corporation has been registered for 5 years, and the second criteria is the corporation has published obligations continously for 5 years. Eight corporations meet those criterias and become the research sample. Data analysis on this research use double regression analysis. The result shows that from five variable researched, only one influence the obligation rank, which is business risk. This result contributes to both theory and praticioners.